Numerical solutions of convective transport on Brinkman-viscoelastic fluid over a bluff body saturated in porous region - Abdul Rahman, Mohd Kasim; Siti Farah Haryatie, Mohd Kanafiah; Syazwani, Mohd Zokri; S., Shafie (Elsevier, 2021)
Convective is a fundamental mechanism in heat transfer analysis. Convective heat transport refers to the transfer of heat from one stage to another. In order to produce the preferred output, it is critical to understand the properties of fluid flow. In this study, mixed convection flow is considered, which is defined as a situation where the forces of pressure and buoyancy interact. The goal of this endeavor is to scrutinize the numerical solution of Brinkman-viscoelastic fluid for mixed convection transport over a horizontal circular cylinder as one of the bluff body geometry. Using the necessary similarity transformation, the governing equations were converted into a less complicated form and numerically solved using Keller-box procedure. The influence of mixed convection, Brinkman and viscoelastic parameters towards the fluid velocity and temperature together with skin friction and heat transfer coefficient is analyzed and demonstrated in graphs and tables. This study has revealed that the distribution of fluid velocity, skin friction and heat transfer coefficient had strengthened due to rising values of mixed convection parameter and declined by virtue of increasing viscoelastic and Brinkman parameters. The temperature profile, on the other hand, clearly demonstrates the increasing trend as the Brinkman and viscoelastic parameter increase and declines because of mixed convection. The results show that all of the significant parameters in this investigation affluence the fluid flow characteristics. The provided theoretical results will develop a thorough understanding on boundary layer issues and will be used as a reference for future research or validation.